Pengaruh kepuasan kerja dan beban kerja terhadap kinerja karyawan pada bagian QA (Quality Assurance) PT Haloni Jane Tangerang - Nurul Alfiani; Mudhita Elviani; Jaka Slameta; Merrisa Fermica Iskandar (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2023)
This study aims to analyse the effect of job satisfaction and workload on employee performance in the QA (Quality Assurance) section of PT Haloni Jane Tangerang. The method in this study uses quantitative methods. Sampling technique using saturated sampling. The number of samples used in this study was 38 employees in the QA (Quality Assurance) section of PT Haloni Jane Tangerang. The data collection method used is using a questionnaire.The results of this study indicate that job satisfaction affects employees in the QA (Quality Assurance) section of PT Haloni Jane Tangerang. This is because the job satisfaction variable has a t value of 3.820 greater than the t table of 2.030 and a significance value of 0.001 less than 0.05. Workload affects employees in the QA (Quality Assurance) section of PT Haloni Jane Tangerang. This is because the workload variable has a t value of 12.014 greater than the t table of 2.030 and a significance value of 0.000 smaller than 0.05. Job satisfaction and workload affect employee performance in the QA (Quality Assurance) section of PT Haloni Jane Tangerang. This is because the job satisfaction variable has a calculated F value of 347.817 greater than the f table of 3.29 and a significance value of 0.000 less than 0.05. The magnitude of the effect of Job Satisfaction and Workload on Employee Performance in the QA (Quality Assurance) section of PT Haloni Jane Tangerang is 95.2%, which means that the contribution of Employee Performance can be explained by the independent variables, namely Job Satisfaction and Workload. Then the remaining 4.8% is explained by other variables not examined in this study.